HIERARCHICALLY STRUCTURED NATURAL FIBRES AS PLATFORM FOR POINT OF CARE ASSAYS - Dedy H.B. Wicaksono (PROSIDING SEMINAR KIMIA, 2015)
Cotton fabric is proposed as an alternative material for low cost point of care devices. Cotton fabrics are vastly available, low cost and flexible. Simple wax patterning method was applied to create hydrophilic channels in cotton fabric. Three-dimensional (3-D) colorimetric microfluidic device was made by folding 2-D pattern along certain predefined lines. 3-D devices show better mixing uniformity between reagents and analyte across the detection zones. On-chip colorimetric calibration is also proposed by putting predefined serially dilutedsamples next to the detection zones. Multiple assays can be integrated within a small surface area by stacking layers of individual assay device separated by a wax-impregnated fabric. Cotton fabric was also used as a platform for conducting Enzyme-Linked Immunosorbent Assay (ELISA). The colorimetric performance is similar to the conventional absorbancebased ELISA, yet with lower cost and shorter time to get results. A second type of device using electrochemical detection principle is also implemented in cotton fabric with three electrode configuration (working, counter and reference electrode), using similar simple and low-cost wax-patterning. In both colorimetric and electrochemical device, comparison with te already popular paper-based device will be discussed. Finally, we present latest results in our lab in which cotton fabrics were used as a novel platform for cell-based assay and cellmanipulationdevice.